2019
DOI: 10.1080/19420862.2018.1558698
|View full text |Cite
|
Sign up to set email alerts
|

Co-engaging CD47 and CD19 with a bispecific antibody abrogates B-cell receptor/CD19 association leading to impaired B-cell proliferation

Abstract: CD19 is a B cell-specific receptor that regulates the threshold of B cell receptor (BCR)-mediated cell proliferation. A CD47xCD19 bispecific antibody (biAb) was generated to target and deplete B cells via multiple antibody-mediated mechanisms. Interestingly, the biAb, constructed of a CD19 binding arm and a CD47 binding arm, inhibited BCR-mediated B-cell proliferation with an effect even more potent than a CD19 monoclonal antibody (mAb). The inhibitory effect of the biAb was not attributable to CD47 binding be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…MEDI5752 leverages cross-arm avidity binding (where one of the fragment antigen binding (Fab) domains acts as an anchor for the other) to take advantage of both the more stable surface expression of PD-1, and the elevated cell surface density of PD-1 vs. CTLA-4. Our data demonstrate enhanced saturation of CTLA-4 with the PD-1/CTLA-4 bispecific when compared to equimolar concentrations of a conventional mAb targeting CTLA-4 and is consistent with recently reported data demonstrating the capacity of bispecific antibodies to promote improved target selectivity by cross-arm avidity binding to two antigens on the surface of the same cell(52)(53)(54)(55)(56)(57)(58). Moreover, we found that tethering PD-1 to CTLA-4 also lead to the internalization and subsequent degradation of PD-1, providing a novel mechanism of action which is distinct from other mAbs targeting this axis.…”
supporting
confidence: 92%
“…MEDI5752 leverages cross-arm avidity binding (where one of the fragment antigen binding (Fab) domains acts as an anchor for the other) to take advantage of both the more stable surface expression of PD-1, and the elevated cell surface density of PD-1 vs. CTLA-4. Our data demonstrate enhanced saturation of CTLA-4 with the PD-1/CTLA-4 bispecific when compared to equimolar concentrations of a conventional mAb targeting CTLA-4 and is consistent with recently reported data demonstrating the capacity of bispecific antibodies to promote improved target selectivity by cross-arm avidity binding to two antigens on the surface of the same cell(52)(53)(54)(55)(56)(57)(58). Moreover, we found that tethering PD-1 to CTLA-4 also lead to the internalization and subsequent degradation of PD-1, providing a novel mechanism of action which is distinct from other mAbs targeting this axis.…”
supporting
confidence: 92%
“…BsAb TG-1801 could potentially overcome the limitation of CD47 monospecific targeting therapy by specifically blocking the 'do not eat me' signal only on B-cells. This is achieved by combining a low-affinity CD47 arm with a high-affinity CD19 arm, thereby reducing the risk of unwanted CD47 blockade in healthy cells (Buatois et al 2018 ; Hatterer et al 2019 ). Similarly, IMM0306, a CD20 x CD47 BsAb developed by ImmuneOnco has achieved remarkable therapeutic effects in various tumor models and showed no binding to human erythrocytes in pre-clinical study (Yu et al 2020 ).…”
Section: Increased Tumor Selectivitymentioning
confidence: 99%
“…Another notable example of a bispecific engager was noted in NI-1701, a CD47/CD19 bispecific antibody constructed with the IgG1 isotype to elicit an ADCP response. This bispecific antibody demonstrated potent in vitro and in vivo activity across a plethora of B cell malignancy models, which rely on the co-engagement of CD47 and CD19 on B cells simultaneously to induce potent ADCP of target cells ( 86 , 87 ).…”
Section: Systematic Engagement Of Macrophages By Bispecific Antibodymentioning
confidence: 99%